Hours with the Bible: or, The Scriptures in the light of modern discovery and knowledge - Geikie, John Cunningham (J. Pott, 1881)
1. From creation to the Patriarchs. -- 2. From Moses to the Judges. -- 3. From Samson to Solomon. -- 4. From Rehoboam to Hezekiah, with the contemporary prophets. -- 5. From Menasseth to Zedekia and contemporary prophets. -- 6. From the exile to Malachi, completing the Old Testament.